Kesadaran Hukum Masyarakat Terhadap Hukum Di Area Publik Kota Medan Dalam Kehidupan Sehari-Hari - Azmiaty Zuliah; Adi Putra; Dian Hardian Silalahi (Universitas Medan Area, 2021)
Public legal awareness in daily life in Indonesia, especially in Medan, still has serious problems. The facts and reality about the increasing number of law violations and deviant actions that are happening are actually happening right before our eyes. These illegal acts and deviant behavior occur not only in certain locations in almost all daily life, especially in big cities. The research used is a combination of a normative juridical approach and a qualitative empirical juridical approach. The purpose of this normative juridical research is to analyze the concept of legal and regulatory concepts that are closely related to the subject matter. The empirical juridical approach is used to see the law as a pattern of community behavior and is seen as a social force in the implementation of legal compliance carried out by people in the city of Medan. The type of data used in this research is primary data obtained through field studies (field research). Research results Public awareness of the law is still weak, it is still finding violations of the law in markets, roads, sidewalks, the environment and public facilities in Medan. Public legal awareness needs to be increased by implementing a legal culture development policy by the government so that compliance with the law can increase